Integrated Reconstructive Management of Periocular Complications Following Bilateral Blepharoplasty - Matilde Tettamanzi, MD; Giovanni Muratore, MD; Federico Ziani, MD; Giovanni Arrica, MD; Claudia Trignano, MD; Corrado Rubino, MD, FEBOPRAS; Emilio Trignano, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. The correction of iatrogenic ectropion of the lower lid represents one of the most complex surgical challenges for the plastic surgeon. These complications compromise both the functionality and aesthetics of the periocular area, and corrective interventions aim to restore the functionality and anatomy of the region. The combination of multiple complications often requires the use of various surgical techniques to resolve the problem. We present the clinical case of a 46-year-old woman who came to our attention following bilateral upper and lower blepharoplasty performed in a private facility by another professional approximately 6 months ago. She presented with third-degree ectropion and lagophthalmos of the left lower eyelid, and second-degree ectropion of the right lower eyelid. Surgical interventions to correct these problems often require skin and cartilage grafts, which often result in recurrences and suboptimal scarring outcomes. The patient expressed reluctance toward the adoption of skin and cartilage grafts taken from another site, so it was decided to opt for correction through a midface lift, lateral canthoplasty, tarsal strip, and conjunctival excision. The follow-up confirmed the success of the surgical procedure, allowing for the correction and restoration of eyelid functionality and aesthetics, without the need for third-party donor sites and with great patient satisfaction.